System and method for testing and grading construction materials - Muniandy, Ratnasamy; Ahmad, Nadzrol Fadzilah; Hassim, Salihudin (2012)
A system for testing and grading a construction material (125) based on multiple properties of the construction material (125) including, one or more test samples of the construction material (125), one or more specimen receptacles (105) for holding the one or more test samples of the construction material (125), an injecting means (110) for extracting and injecting the one or more test samples of the construction material (125) into the one or more specimen receptacles (105), a heating means for heating the one or more test samples of the construction material at a first temperature, and a supporting means (120) including multiple gaps (123). The system further includes one or more analyzers for analyzing the one or more test samples of the construction material (125) contained inside the one or more specimen receptacles (105).